DESIGN ACCOUNTING RECORDING AND FINANCIAL REPORTING SYSTEM AT TOKO TOYS GARDEN - Cindy Francesca; Anita Anita (Universitas Internasional Batam, 2022)
The purpose of the study was to design an accounting record-keeping system for Toys Garden Store owner. The Toys Garden store has been operating for four years but does not yet have accurate and efficient Microsoft Office Access record keeping. Toys Garden stores only have a manual recording in the book, so the record-keeping is still considered quite messy. Manual accounting records will make it harder to track a company's cash flow because it can take a considerable amount of time to make financial statements each period. Over time, the use of the system will facilitate the preparation and creation of financial statements more efficiently and effectively without having to enter them manually. The author will design a financial system using the Microsoft Office Access accounting system to be able to manage the company's financial condition so that it can see expenses, revenues, and control all data that can affect the company's finances. The author will make a plan by the needs of the Toys Garden Store and create an account list form, customer list form, vendor list form, item list form, asset list form, purchase form, and sales form to present account list report, asset depreciation report, asset list report, income statement, statement of owner equity financial position, cash flow statement, purchase report, sales report, inventory report, payable report, receivable report, ledger report and after designing the system continued implementation of Toys Garden Store so that it knows the system can run properly and minimize errors. Thus, the design of the Microsoft Office Access accounting system can provide a positive relationship for toys garden stores because it has an inventory card that can help quickly check for bicycle supplies.